2015
DOI: 10.3329/bpj.v18i2.24312
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of the Role of Community Pharmacists in Dhaka city, Bangladesh

Abstract: Community pharmacists play a vital role in improving medication safety and better healthcare facility to the community. Unfortunately, the field of community pharmacy in Bangladesh is still to be developed and there is scarcity of data regarding current role of community pharmacists in Bangladesh. The present study was conducted to find out the role of community pharmacists in Bangladesh. For the study purpose, we visited 42 retail pharmacies in Banani, Khilkhet and Uttra areas of Dhaka city and interviewed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…Among the medical tests commonly conducted by community pharmacists were blood pressure, glucose and pregnancy tests. The educational activities conducted by community pharmacists for their patients as part of the public health activities were consistent with the activities provided by the community pharmacists in other low- and middle-income countries [31]. Agomo et al reported that the literature revealed that services such as smoking cessation, health promotion, provision of hormonal contraceptives and preventive activities provided by pharmacists have benefited the community [32].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Among the medical tests commonly conducted by community pharmacists were blood pressure, glucose and pregnancy tests. The educational activities conducted by community pharmacists for their patients as part of the public health activities were consistent with the activities provided by the community pharmacists in other low- and middle-income countries [31]. Agomo et al reported that the literature revealed that services such as smoking cessation, health promotion, provision of hormonal contraceptives and preventive activities provided by pharmacists have benefited the community [32].…”
Section: Discussionmentioning
confidence: 66%
“…By offering these screening tests, the community pharmacists may assist patients with diagnosis and therapy. The provided medical tests were similar to the services offered by community pharmacists in Dhaka, Bangladesh [31].…”
Section: Discussionmentioning
confidence: 99%
“…In developing countries like BANGLADESH, people depend more on pharmacies due to expediency, shorter waiting time, cost reduction, availability of credit and flexible opening hours [ 11 , 12 ]. Here some drug seller also provide clinical services to patients with chronic disease even manages mild non severe trauma [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Though there are previous studies in BANGLADESH which demonstrated increased self medication tendency [ 14 ] and role of community pharmacists [ 13 ] but this was the first study which focused on both drug dispensing pattern of the pharmacy and tried to shed light on the contribution of pharmacies in irrational drug use.…”
Section: Introductionmentioning
confidence: 99%
“…21 About 51.5% of the pharmacists engaged in health screening activities, such as blood pressure measurement, the result is comparable with the study carried out in Aden city 9 and in Bangladesh. 22 The community pharmacies rarely or seldom created a personal medication record for their customers. The reporting and documenting of the patient's history is a must because it helps to monitor the progress of the disease, reporting any adverse drug reaction and other drug-related problems.…”
Section: Discussionmentioning
confidence: 99%